Bare-knuckle Britons and fighting Irish : boxing, race, religion and nationality in the 18th and 19th centuries - Chill, Adam (McFarland & Company, Inc., Publishers, 2017)
"Boxing was phenomenally popular in 18th and 19th century Britain. Aristocrats attended matches and patronized boxers, and the most important fights drew tens of thousands of spectators. This history focuses on how boxers, journalists, politicians, pub owners and others used national, religious and racial identities to promote pugilism and its pure English pedigree"--